Role of 1α,25-Dihydroxyvitamin D3 in Adipogenesis of SGBS Cells: New Insights into Human Preadipocyte Proliferation - Felicidade, Ingrid [UNESP] (2018)
Background/Aims: Compared with non-obese individuals, obese individuals commonly store more vitamin D in adipose tissue. VDR expression in adipose tissue can influence adipogenesis and is therefore a target pathway deserving further study. This study aims to assess the role of 1,25(OH)2D3 in human preadipocyte proliferation and differentiation. Methods: RTCA, MTT, and trypan blue assays were used to assess the effects of 1,25(OH)2D3 on the viability, proliferation, and adipogenic differentiation of SGBS cells. Cell cycle and apoptosis analyses were performed with flow cytometry, triglycerides were quantified, and RT-qPCR was used to assess gene expression. Results: We confirmed that the SGBS cell model is suitable for studying adipogenesis and demonstrated that the differentiation protocol induces cell maturation, thereby increasing the lipid content of cells independently of treatment. 1,25(OH)2D3 treatment had different effects according to the cell stage, indicating different modes of action driving proliferation and differentiation. In preadipocytes, 1,25(OH)2D3 induced G1 growth arrest at both tested concentrations without altering CDKN1A gene expression. Treatment with 100 nM 1,25(OH)2D3 also decreased MTT absorbance and the lipid concentration. Moreover, increased normalized cell index values and decreased metabolic activity were not induced by proliferation or apoptosis. Exposure to 100 nM 1,25(OH)2D3 induced VDR, CEBPA, and CEBPB expression, even in the preadipocyte stage. During adipogenesis, 1,25(OH)2D3 had limited effects on processes such as VDR and PPARG gene expression, but it upregulated CEBPA expression. Conclusions: We demonstrated for the first time that 1,25(OH)2D3 induces changes in preadipocytes, including VDR expression and growth arrest, and increases the lipid content in adipocytes treated for 16 days. Preadipocytes are important cells in adipose tissue homeostasis, and understanding the role of 1,25(OH)2D3 in adipogenesis is a crucial step in ensuring adequate vitamin D supplementation, especially for obese individuals.